Obszary poprzemysłowe w nowych realiach gospodarczych na przykładzie Nowej Rudy - Korenik, Stanisław; Rogowska, Małgorzata (Post-Industrial Areas in New Economic Realities on the Example of Nowa Ruda, 2008)
Changes begun in the early nineties of the 20th Century, basing mainly on building new economy caused a decrease in the impact of traditional industry, which can be easily noticed in the emergance of extensive post-industrial areas in Polish cities. Closing stone coal mines caused many problems not only on economic background but on social situation as well. The article concerns the problem of restructuring and revitalization thise extensive areas on the example of Nowa Ruda. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 322-328